Integrating groundwater irrigation into hydrological simulation of India: Case of improving model representation of anthropogenic water use impact using GRACE - Xie, Hua; Longuevergne, L.; Ringler, Claudia; Scanlon, Bridget R. (Elsevier, 2020)
India boasts the largest irrigated agricultural system in the world relying on groundwater. To address the strong linkages between the natural groundwater and the anthropogenic irrigated system requires innovative hydrological modeling geared at informing national policies on groundwater management and future development of irrigated agriculture. For this, we developed a predictive, integrated hydrological and groundwater use model and evaluated the model using total water storage (TWS) data from the Gravity Recovery and Climate Experiment (GRACE). The utility of the model was demonstrated in a case study in which the model was applied to project the groundwater balance in northwest India under four RCP (Representative Concentration Pathways) scenarios.